Welding characteristics of similar and dissimilar metal welding - Lim Yuan Ting (School of Materials Engineering, University Malaysia Perlis, 2016)
The two main concern areas of weld nugget quality from resistance spot welding processes for galvanized steel joints and galvanized steel with stainless steel joints. This project analyzed only the quality of weld nugget growth on similar and dissimilar with respect to variation of weld current. The work carried out in two stages. First stages, dealing with the welding of galvanized steel together which as similar metal joints. Second stage is dealing with the welding of galvanized steel and stainless steel which as dissimilar metal joints. Both are using lap joints techniques. The welded samples were all equal in size for hardness test and metallurgical analysis to characterise the weld nugget formation. The hardness distributions were measured from the heat affected zones, base metal and fusion zones. Microstructural of base metal, fusion and HAZs were observed.